2013
DOI: 10.1212/wnl.0b013e31829bfd8f
|View full text |Cite
|
Sign up to set email alerts
|

Using iron oxide nanoparticles to diagnose CNS inflammatory diseases and PCNSL

Abstract: Objective: The study goal was to assess the benefits and potential limitations in the use of ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles in the MRI diagnosis of CNS inflammatory diseases and primary CNS lymphoma.Methods: Twenty patients with presumptive or known CNS lesions underwent MRI study. Eighteen patients received both gadolinium-based contrast agents (GBCAs) and 1 of 2 USPIO contrast agents (ferumoxytol and ferumoxtran-10) 24 hours apart, which allowed direct comparative analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…The uptake of USPIOs by phagocytic monocytes and macrophages provides an in vivo tool by which MRI can be used to monitor the involvement of macrophages in inflammatory processes, such as multiple sclerosis (MS), stroke, brain tumors, and vulnerable plaque in carotid artery (1,(92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Uspio Enhanced Mri For Inflammation Process Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of USPIOs by phagocytic monocytes and macrophages provides an in vivo tool by which MRI can be used to monitor the involvement of macrophages in inflammatory processes, such as multiple sclerosis (MS), stroke, brain tumors, and vulnerable plaque in carotid artery (1,(92)(93)(94)(95)(96)(97)(98)(99).…”
Section: Uspio Enhanced Mri For Inflammation Process Evaluationmentioning
confidence: 99%
“…This infiltration was associated with local higher loss of tissue structure and persistent local loss of tissue structure. Farrell et al (97) reported that ferumoxytol or ferumoxtran-10-enhanced brain MRI can be useful in the diagnosis of central nerve system inflammatory disorders (demyelination or inflammation) and lymphoma (lymphoma or lymphoproliferative disorder), and is also useful for patients with renal compromise at risk of nephrogenic systemic fibrosis who are unable to receive GBCA.…”
Section: Uspio Enhanced Mri For Inflammation Process Evaluationmentioning
confidence: 99%
“…23 Furthermore, there is potentially a requirement of 2 consecutive days of imaging to obtain relatively intracellular-weighted or interstitial-weighted images, the scans that would be more analogous to the gadolinium-based anatomical scans. 24 The use of a bidirectional leakage correction model changed the estimated rCBV values significantly compared to both the standard unidirectional leakage correction model and rCBV measured without leakage correction, despite relatively short DSC-MRI acquisition times. The change from pretreatment baseline in rCBV estimated using the Bidir-model 2 months after bevacizumab therapy in recurrent GBM stratified patients according OS, whereas uncorrected and standard Unidir-model estimates of change in rCBV did not.…”
Section: Discussionmentioning
confidence: 92%
“…There are no specific features, which allow a reliable differentiation between PCNSL and other primary or secondary brain tumors as well as inflammatory lesions. The use of ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles may improve the MRI diagnosis of PCNSL [4]. This technique, however, has not yet entered the clinical routine examination.…”
Section: Introductionmentioning
confidence: 99%